A Small Multihost Plasmid Carrying erm(T) Identified in Enterococcus faecalis - Li, Xing-Yun; Yu, Rui; Xu, Chunyan; Shang, Yanhong; Li, Dexi; Du, Xiang-Dang (Frontiers in Veterinary Science, 2022)
The aim of this study was to determine the mobile genetic elements involved in the horizontal transfer of erm(T) in Enterococcus faecalis, and its transmission ability in heterologous hosts. A total of 159 erythromycin-resistant enterococci isolates were screened for the presence of macrolide resistance genes by PCR. Whole genome sequencing for erm(T)-carrying E. faecalis E165 was performed. The transmission ability in heterologous hosts was explored by conjugation, transformation and fitness cost. The erm(T) gene was detected only in an E. faecalis isolate E165 (1/159), which was located on a 4244-bp small plasmid, designed pE165. Using E. faecalis OG1RF as the recipient strain, pE165 is transferable. Natural transformation experiments using Streptococcus suis P1/7 and Streptococcus mutans UA159 as the recipients indicated it is transmissible, which was also observed by electrotransformation using Staphylococcus aureus RN4220 as recipient. The erm(T)-carrying pE165 can replicate in the heterologous host including E. faecalis OG1RF, S. suis P1/7, S. mutans UA159 and S. aureus RN4220 and conferred resistance to erythromycin and clindamycin to all hosts. Although there is no disadvantage of pE165 in the recipient strains in growth curve experiments, all the pE165-carrying recipients had a fitness cost compared to the corresponding original recipients in growth competition experiments. In brief, an erm(T)-carrying plasmid was for the first time described in E. faecalis and transmissible to heterologous hosts.